The Impact of Multidisciplinary Conferences on Healthcare Utilization in Chronic Pain Patients - Campwala, Zahabiya; Davis, Gregory; Khazen, Olga; Trowbridge, Rachel; Nabage, Melisande; Bagchi, Rohan; Argoff, Charles; Pilitsis, Julie G. (Frontiers in Pain Research, 2021)
Approximately 100 million adults in the United States have chronic pain, though only a subset utilizes the vast majority of healthcare resources. Multidisciplinary care has been shown to improve outcomes in a variety of clinical conditions. There is concern that multidisciplinary care of chronic pain patients may overwhelm existing resources and increase healthcare utilization due to the volume of patients and the complexity of care. We report our findings on the use of multidisciplinary conferences (MDC) to facilitate care for the most complex patients seen at our tertiary center. Thirty-two of nearly 2,000 patients seen per year were discussed at the MDC, making up the top 2% of complex patients in our practice. We evaluated patients' numeric rating score (NRS) of pain, medication use, hospitalizations, emergency department visits, and visits to pain specialists prior to their enrollment in MDC and 1 year later. Matched samples were compared using Wilcoxon's signed rank test. Patients' NRS scores significantly decreased from 7.64 to 5.54 after inclusion in MDC (p < 0.001). A significant decrease in clinic visits (p < 0.001) and healthcare utilization (p < 0.05) was also observed. Opioid and non-opioid prescriptions did not change significantly (p = 0.43). 83% of providers agreed that MDC improved patient care. While previous studies have shown the effect of multi-disciplinary care, we show notable improvements with a team established around a once-a-month MDC.